1986
DOI: 10.1016/s0735-1097(86)80338-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of skeletal muscle hypoperfusion during exercise using phosphorus-31 nuclear magnetic resonance spectroscopy

Abstract: Blood flow to working skeletal muscle is frequently reduced in patients with heart failure or peripheral vascular disease. To determine if phosphorus nuclear magnetic resonance (NMR) can noninvasively detect such muscle underperfusion, gated phosphorus-31 NMR spectroscopy was used to compare muscle inorganic phosphate, phosphocreatine and pH during mild wrist flexion exercise at 0.2, 0.4 and 0.6 W in eight normal men, before and after reduction of forearm blood flow. Forearm flow was reduced by cuff inflation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…These findings are in accordance with other studies that have demonstrated delayed regeneration of PCr as a reliable marker of arterial obstruction (12,17,24,25). When compared with normal subjects in our study, there was an approximate three-fold increase in the recovery time constant among patients.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with other studies that have demonstrated delayed regeneration of PCr as a reliable marker of arterial obstruction (12,17,24,25). When compared with normal subjects in our study, there was an approximate three-fold increase in the recovery time constant among patients.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in accordance with other studies that have demonstrated delayed regeneration of PCr as a reliable marker of arterial obstruction. 13,58,65,66 When compared with normal subjects in our study, there was an approximate 3-fold increase in the recovery time constant among patients. The area under the fitted curve of the ROC analysis is 0.925, demonstrating that PCr recovery kinetics can be used to discriminate mild to moderate symptomatic PAD patients from normals.…”
Section: Pcr Recovery Kinetics After Exercisesupporting
confidence: 42%
“…During submaximal exercise, a reduction of oxygen delivery to exercising skeletal muscle results in a higher Pi/PCr and greater lactate production (22). Since the peripheral blood flow response to exercise in CHF is inappropriately low (18,23), an increase in blood flow could be expected to improve exercise metabolism.…”
Section: Discussionmentioning
confidence: 99%